Evaluation of the Performance of Modified Surface Dressing with Environmental Waste in the Context of Aggregate-Bitumen Relationship - Akalın, Kadir Berkhan; Karacasu, Murat (Fırat University, 2020)
Road pavements are produced in the form of Bituminous Hot Mix Asphalt (HMA) or surface dressing in general. In this study, the aggregate-bitumen relationship of surface dressing, which is preferred more due to its low cost, was investigated. Surface dressing cost is much lower than HMA. Therefore, it is used more than the HMA. Surface dressing is more affected by climatic changes. However, surface dressing manufactured with suitable designs can serve during their service life. In experimental studies, aggregate, bitumen and mixture test results were evaluated together. Limestone and basalt aggregates were used as the aggregates. As the bitumens; 50/70 and 70/100 penetration grade bitumens, as an additive; 10% waste rubber and 1% PVC are used in the experiments. Peeling resistance and adhesion (Vialit plate) tests were applied to measure the performance. According to the experimental results; in the adhesion (Vialit) tests, the performance of limestone samples was found to be better than basalt samples. 50/70 penetration grade bitumen provides better adhesion with limestone aggregates, while 70/100 bitumen provides better adhesion in basalt aggregates. Waste rubber and PVC fibers increase adhesion strength between aggregate and bitumen. In addition, the wastes used as additives revel a good performance when the limestone is used as an aggregate. Waste rubber and PVC fibers increase the adhesion strength which is low in basalt aggregates especially. In 70/100 penetration grade bitumen, the homogeneous dispersion of the wastes as the additives is facilitated due to the consistency of the bitumen, thus increasing the adhesion strength can be easily observed. In the context of peeling strength, limestone aggregates and the bitumen modified by the waste rubber provided the best performance.

: Karayolu üstyapı kaplamaları genel olarak Bitümlü Sıcak Karışım (BSK) veya sathi kaplama şeklinde üretilmektedir. Bu çalışmada düşük maliyeti sebebiyle kullanım alanı fazla olan sathi kaplamaların agrega-bitüm ilişkisi incelenmiştir. Yapılan çalışmalarda, agrega, bitüm ve karışım deney sonuçları birlikte değerlendirilmiştir. Agrega olarak kireçtaşı ve bazalt cinsi agregalar kullanılmıştır. Bitüm olarak; 50/70 ve 70/100 penetrasyonlu bitümler, katkı olarak ise; % 10 atık lastik ve %1 Polivinil Klorür (PVC) kullanılmıştır. Üretilen bütün bu farklı tipteki numuneler için sathi kaplamaların performansının ölçülmesinde kullanılan Soyulma ve Yapışma (Vialit) mukavemeti deneyleri gerçekleştirilmiştir. Deneysel çalışmalardan elde edilen sonuçlara göre, 50/70 bitüm kireçtaşı agregalarla daha iyi yapışma sağlarken, 70/100 bitüm bazalt agregalarda daha güçlü yapışma sağlamaktadır. Atık lastik ve PVC talaşları agrega ve bitüm arasındaki adezyonu artırmaktadır. Ayrıca atıklar kireçtaşı agregalarda daha iyi performans göstermektedir. Özellikle bazalt türü agregalarda düşük olan adezyonu, kullanılan atık lastik ve PVC talaşları artırmaktadır. 70/100 penetrasyonlu bitümde, bitümün kıvamından dolayı katkı olarak kullanılan atıkların homojen dağılmaları kolaylaşmakta ve bu sayede adezyon kuvvetindeki artış daha iyi gözlenebilmektedir. Soyulma mukavemeti kapsamında, atık lastik ile modifiye edilmiş olan bitüm ve kireçtaşı en iyi performansı sağlamıştır.
Çevresel Atıklarla Modifiye Edilmiş Sathi Kaplamaların Performansının Agrega-Bitüm İlişkisi Bağlamında Değerlendirilmesi